Percutaneous fixation with Kirschner wires versus volar locking-plate fixation in adults with dorsally displaced fracture of distal radius: five-year follow-up of a randomized controlled trial. (August 2019) - Costa, M. L.; Achten, J.; Rangan, A.; Lamb, S. E.; Parsons, N. R.
Abstract : Aims: The aim of this study was to compare the clinical effectiveness of Kirschner wire (K-wire) fixation with locking-plate fixation for patients with a dorsally displaced fracture of the distal radius in the five years after injury. Patients and Methods: We report the five-year follow-up of a multicentre, two-arm, parallel-group randomized controlled trial. A total of 461 adults with a dorsally displaced fracture of the distal radius within 3 cm of the radiocarpal joint that required surgical fixation were recruited from 18 trauma centres in the United Kingdom. Patients were excluded if the surface of the wrist joint was so badly displaced it required open reduction. In all, 448 patients were randomized to receive either K-wire fixation or locking-plate fixation. In the K-wire group, there were 179 female and 38 male patients with a mean age of 59.1 years (19 to 89). In the locking-plate group, there were 194 female and 37 male patients with a mean age of 58.3 years (20 to 89). The primary outcome measure was the patient-rated wrist evaluation (PRWE). Secondary outcomes were health-related quality of life using the EuroQol five-dimension three-level (EQ-5D-3L) assessment, and further surgery related to the index fracture. Results: At 12 months, 402/448 participants (90%) recruited into the main study provided PRWE scores. At year two, 294 participants (66%) provided scores; at year five, 198 participants (44%) provided scores. There was no clinically relevant difference in the PRWE at any point during the five-year follow-up; at five years, the PRWE score was 8.3 (12.5) in the wire group and 11.3 (15.6) in the plate group (95% confidence interval -6.99 to 0.99; p = 0.139). Nor was there a clinically relevant difference in health-related quality of life. Only three participants had further surgery in the five years after their injury (one in the wire group and two in the plate group). Conclusion: This follow-up study continues to show no evidence of a difference in wrist pain, wrist function, or quality of life for patients treated with wires versus locking plates in the five years following a dorsally displaced fracture of the distal radius. Cite this article: Bone Joint J 2019;101-B:978–983.